PENGARUH PEMIMPIN TERHADAP KEBERHASILAN PENANAMAN GEREJA MENURUT KITAB KISAH PARA RASUL - Yohanes Gijs Pany (STT Ekklesia Pontianak, 2026)
Abstract: Leadership is the key to the progress of an institution, including the church as a ministry institution. Weak church leadership will have a negative impact on church development. The early church, which the book of Acts states is a model for today's church in terms of its growth strategies, Theologically, the growth of the early church was the work of the Holy Spirit pouring out His power. The book Acts 1:8 expresses it this way: